Perbedaan asupan energi dan zat gizi makro berdasarkan kejadian risiko KEK pada ibu hamil - Rifki, Muhammad Ainur; Sitoayu, Laras; Gifari, Nazhif; Nuzrina, Rachmanida; Ronitawati, Putri (Jurnal Gizi Klinik Indonesia, 2022)
The differences in energy and macronutrient intake based on risk of chronic energy deficiency for pregnant womenBackground: Pregnancy is an essential period in forming the quality of human resources that requires adequate intake of energy and macronutrients for development and growth in the fetus and maintaining nutritional status in pregnant women.Objective: The study aims to determine the differences in energy and macronutrient intake based on chronic energy deficiency (CED), a condition characterized by long-term inadequate energy intake, among pregnant women in Bengkulu Province.Method: This research was used in a cross-sectional research design. The number of samples was 1,167 respondents, taken using total sampling techniques and conducted in Bengkulu Province. The data used secondary data from the Republic of Indonesia's Ministry of Health Survey in 2016. Data analysis in the study used the Mann-Whitney test and multiple logistic regression.Results: The results of this research show the average intake of energy, protein, fat, and carbohydrates in respondents who are at risk of CED respectively are 1,478±48 kcal; 53±2 g; 30±2 g; 24±9 g; and for the average intake of respondents who are not the risk of CED respectively are1,647±18 kcal; 58±1 g; 34±1 g; 262±3 g. The results showed that there was a difference between energy intake (p=0.013), protein (p=0.035), and carbohydrate (p=0.035) based on the incidence of CED risk in pregnant women.Conclusion: Based on the dietary intake analysis of pregnant women, there were differences between the risk of CED and those not at risk of CED. Therefore, pregnant who risk CED must be given a balanced diet (energy and macronutrients) to improve their nutritional status during pregnancy.